Stability of supported aerosol-generated nanoparticles in liquid media - Sara M. Franzén (Nature Portfolio, 2021)
Abstract The stability of nanoparticles and their supports are critical, but poorly understood, parameters for applications of such systems in liquid environments. Here we develop an approach to systematically investigate the stability of aerosol-generated nanoparticles after exposure to commonly used solvents using a combination of identical location-SEM and density/size analysis. We demonstrate that the choice of solvent needs to be carefully matched with both the particle and support materials. We show that thermal annealing significantly increases the adhesion of the particles and expands the scope of applications in aqueous media and for biological applications. The results clarify combinations of inorganic nanoparticles on oxide and semiconductor supports with solvents and environmental conditions that give sufficient stability. Combined, the presented methods should be of value in investigating the stability of nanoparticle systems after exposure to solvent and can be used for future developments of high-performing supported aerosol-generated nanoparticles for solvent-based applications.